MECHANISMS FOR ENSURING INFORMATION SECURITY IN THE DIGITAL SOCIETY (Scientific journal of the Fergana State University, 2026)
This article studies the theoretical and methodological foundations of ensuring information security in the digital society, the process of ensuring personal information security in the transformation of national sites. It also examines the proportionality of the transformation of national sites to the deepening of democratic reforms and the impact of national sites on the formation of public opinion in the digital society. In addition, it identifies social factors that affect the process of ensuring information security of national sites on the Internet and indicates the content of modern mechanisms for improving the activities of national sites in the new Uzbekistan. At the same time, scientifically based proposals have been developed to ensure information security in the digital society.